IMPLEMENTATION OF POLICIES IN HANDLING THE HOMELESS IN LHOKSEUMAWE CITY - Zulaifah Ulaiya; Muklir; Bobby Rahman; Cut Sukmawati; Asrul Fahmi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The emergence of homeless people in Lhokseumawe City is influenced by structural factors, especially the economic system that causes some people to be marginalized and unable to meet basic needs. Aceh Qanun Number 11 of 2013 concerning Social Welfare, specifically Articles 45 and 46 paragraph (1), requires local governments to address this problem. This study aims to analyze the Lhokseumawe City Government's policy in handling homeless people through the Social Service, and identify the obstacles faced. The method used is descriptive qualitative, with data collection through observation, interviews, and documentation. Data analysis is carried out through reduction, presentation, and drawing conclusions. The results of the study indicate that the implementation of the Qanun has not been effective, characterized by budget limitations, minimal facilities such as shelters, and a lack of ongoing development. External obstacles include cultural influences, minimal family support, and low public awareness. The conclusion of the study confirms that this policy has not been able to significantly reduce the number of homeless people. Recommendations include strengthening cross-sector coordination, and providing adequate social rehabilitation facilities to support the reintegration of homeless people into society.